1968
DOI: 10.1037/h0026777
|View full text |Cite
|
Sign up to set email alerts
|

Mirror-image stimulation.

Abstract: The psychological properties of an organism's own reflection in a mirror are analyzed in some detail. Methodological problems associated with mirror research are also discussed. Many organisms are responsive to mirrors, and reflected images are examined in terms of motivational and social stimulus properties which have been found to extend across a wide variety of species. Reinforcing properties of mirrors are interpreted in terms of novel stimulation with social stimulus overtones. Stimulus change and mimicry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
92
0
3

Year Published

1971
1971
2007
2007

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 181 publications
(97 citation statements)
references
References 45 publications
2
92
0
3
Order By: Relevance
“…Similar results were obtained in a French "field study" in which 15 female retardates (MA .75 to 3.33) demonstrated equivocal reactions when placed in front of a mirror (Shentoub, SouIairac, & Rustin, 1955). Collectively, these findings indicate that, for these subjects, mirror-image stimulation is not intrinsically reinforcing, as predicted by Gallup (1968), and that PMRs rank somewhat below adolescent chimpanzees (Gallup, 1970;Gallup, McClure, Hill, & Bundy (1971) and orangutans (Lethmate & Ducker, cited in Gallup, Boren, Gagliardi, & Wallnau, in press) in the ability to make "self-directed" responses in the presence of a mirror. Similar negative results were obtained when a crabeating macaque was given 2,400 h of mirror exposure (Gallup, in press).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Similar results were obtained in a French "field study" in which 15 female retardates (MA .75 to 3.33) demonstrated equivocal reactions when placed in front of a mirror (Shentoub, SouIairac, & Rustin, 1955). Collectively, these findings indicate that, for these subjects, mirror-image stimulation is not intrinsically reinforcing, as predicted by Gallup (1968), and that PMRs rank somewhat below adolescent chimpanzees (Gallup, 1970;Gallup, McClure, Hill, & Bundy (1971) and orangutans (Lethmate & Ducker, cited in Gallup, Boren, Gagliardi, & Wallnau, in press) in the ability to make "self-directed" responses in the presence of a mirror. Similar negative results were obtained when a crabeating macaque was given 2,400 h of mirror exposure (Gallup, in press).…”
Section: Discussionmentioning
confidence: 93%
“…It was hypothesized that these modifications would lead to demonstrations of self-recognition as predicted by mirror-image stimulation theory (Gallup, 1968) and studies which have reported the presence of the ability among MA-matched normal infants (e.g., Gesell & Ames, 1947).…”
mentioning
confidence: 99%
“…[Gallup (1968), for example, has discussed the numerous important differences between mirror stimuli and the stimuli provided by live animals.] The second experiment was essentially a replication of the first, except that live fish were substituted for mirror images.…”
Section: Experiments IImentioning
confidence: 99%
“…Mirror-image stimulation experimentally confronts the tested animal with an opponent on its territory that is symmetric in size, motivation, and behavioural output, therefore forming a constant aggressive reinforcement for the tested animal [e.g. Gallup, 1968;Thompson, 1966]. Probably, since in a normal confrontation with a conspecific no such strict continuity in reciprocity exists, the readiness to show aggressive display to a mirror image has been found to be somewhat higher to a mirror-image than to a conspecific [Dore et al, 1978].…”
Section: Introductionmentioning
confidence: 99%